Galéria Medium : Rocenka 1992. - Galéria Medium, Bratislava (Bratislava : Galeria Medium, 1993)
Kostka, Jozef ; Kuroda, Aki ; Amos Komenský, Ján ; Pálffy, Peter ; Courtois, Pierre ; Sokol, Koloman ; etc.
Slovaaks & Engels & Duits & Frans
boek